A conceptual and empirical validation of the household lifecycle concept in South Africa - J. Van Rooyen; P. J. Du Plessis (SA Journal of Industrial Psychology, 2003)
The family life cycle theory was used in the research as a tool for segmenting markets and developing marketing strategy. Households are not always family based and can take the form of single households, same gender households, and cohabiter-type households, each displaying distinctly different consumption behaviours. The researchers investigated whether the household life cycle theory is a valuable basis for segmentation in the South African environment. The results indicated that although the household life cycle theory has proven useful in differentiating between households in their consumption behaviour, it should not be used exclusively in segmenting markets due to the high level of within-stage heterogeneity. Opsomming Die gesinslewensikluskonsep is as ’n hulpmiddel gebruik in marksegmentering om bemarkingstrategieë te ontwikkel. Huishoudings is egter nie altyd gesins-gebaseerd nie en kan bestaan uit enkel-, dieselde geslag-, en saamblyhuishoudings wat elkeen merkbare verskille kan toon ten opsigte van verbruikspatrone. Ondersoek is gedoen oor die huishoudingslewensiklusteorie as basis vir marksegmentering in die Suid-Afrikaanse omgewing. Die resultate dui daarop dat ofskoon die huishoudingslewensiklus bruikbaar is om tussen huishoudings te differensieer in terme van verbruiksgedrag, diè teorie nie uitsluitlik en in isolasie gebruik moet word nie vanweë die hoë vlak van binne-stadium verskillendheid.